Serial assessment of functional recovery following nerve injury using implantable thin‐film wireless nerve stimulators. Issue 6 (6th October 2016) - Gamble, Paul; Stephen, Manu; MacEwan, Matthew; Ray, Wilson Z.
ABSTRACT: Introduction : Comprehensive assessment of the time course of functional recovery following peripheral nerve repair is critical for surgical management of peripheral nerve injuries. This study describes the design and implementation of a novel implantable wireless nerve stimulator capable of repeatedly interfacing peripheral nerve tissue and providing serial evaluation of functional recovery postoperatively. Methods : Thin‐film wireless implants were fabricated and subcutaneously implanted into Lewis rats. Wireless implants were used to serially stimulate rat sciatic nerve and assess functional recovery over 3 months following various nerve injuries. Results : Wireless stimulators demonstrated consistent performances over 3 months in vivo and successfully facilitated serial assessment of nerve and muscle function following nerve crush and nerve transection injuries. Conclusions : This study highlights the ability of implantable wireless nerve stimulators to provide a unique view into the time course of functional recovery in multiple motor targets. Muscle Nerve 54 : 1114–1119, 2016